Long-term follow-up of photocoagulated retinal breaks. Issue 4 (April 1978) - Romem, M.; Singer, L.
Abstract : 126 cases of retinal breaks treated in our department by photocoagulation during a period of 10 years (1963-1973) were selected for a close annual follow-up. Eliminated from the study were cases of macular holes, breaks which developed in an eye after retinal detachment surgery, and cases in which a close follow-up was impossible for various reasons. The study includes symptomatic retinal breaks in myopic, non-myopic, and aphakic eyes as well as asymptomatic holes which were found in the undetached fellow eye. Four eyes treated by photocoagulation (3.2%) developed a retinal detachment. The causes of failures and complications, such as retinal detachment, vitreous haemorrhage, and macular pucker, are discussed.